BATIK HOUSE CEMPAKA SALES IN APPLICATION USING THE MICROSOFT VISUAL BASIC 6.0 - Endra Sulistyawan (Jurnal Sistem Informasi, 2010)
This scholarly work contains a simple application program on computerizedsales and inventory at the House of Batik Cempaka. The system work is by using theinput data items that are available and the sale process, which will then automaticallystored in a database and display the output results will come out that will be received by thebuyer or customers as a receipt or purchase receipt and viewing of reports required by theowner of these stores.The process of inputting the computerized sales and this makes data processingmore efficient and accurate and can provide information on existing inventory.The need of information is very important, especially in the business world. Theauthor hopes with the construction of this application at House of Batik Cempaka, thenthe information about inventory and sales of goods can be presented well.